The Multi of Wildlife in The Nam Ha National Protected Area in The Border Between Nam Kong River and Sung Yong Park in China - SOUKANYA, KongKeo; INTHALEUXAY , Sysomphou (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
This survey was carried out to study amount and density of wild animals by using the camera digital to recording their behavior at Namha national protected area in the Namtha province. The results recorded by photography that there were 12 types and had included 233 heads of wild animals such as 48 heads of monkey; birds =34; tinnitus = 34; tiffany = 19; wild pigs = 29; deer = 19; dogs = 16; walls = 14; chickens= 12; Tons = 6; squirrel = 1 and bear = 1. The density of areas were included that monkey = 0.222head per m2 (20.6%); birds = 0.157 (14.6%); tinnitus = 0.157; wild pigs = 0.134 (12.4%); deer = 0.087 (8.15%); tiffany = 0.087 (8.15%); dogs = 0.074 (6.86%); walls = 0.064 (0.06%); chickens = 0.055 (5.15%); Tons = 0.027 (2.57%); squirrels = 0.004 (0.42%) and bears = 0.004head per m2 (0.42%) respectively.